BK channel overexpression on plasma membrane of fibroblasts from Hutchinson-Gilford progeria syndrome - Zironi, Isabella (Aging (Albany NY), 2018)
Hutchinson-Gilford progeria syndrome (HGPS) is an extremely rare genetic disorder wherein symptoms resembling aspects of aging are manifested at a very early age. It is a genetic condition that occurs due to a de novo mutation in the LMNA gene encoding for the nuclear structural protein lamin A. The lamin family of proteins are thought to be involved in nuclear stability, chromatin structure and gene expression and this leads to heavy effects on the regulation and functionality of the cell machinery. The functional role of the large-conductance calcium-activated potassium channels (BK(Ca)) is still unclear, but has been recently described a strong relationship with their membrane expression, progerin nuclear levels and the ageing process. In this study, we found that: i) the outward potassium membrane current amplitude and the fluorescence intensity of the BK(Ca) channel probe showed higher values in human dermal fibroblast obtained from patients affected by HGPS if compared to that from healthy young subjects; ii) this result appears to correlate with a basic cellular activity such as the replicative boost. We suggest that studying the HGPS also from the electrophysiological point of view might reveal new clues about the normal process of aging.